Diet in pregnant teenagers with hypertension: Care and Culture - Gómez-Domínguez, Wendy Johana (Universidad y Salud, 2021)
Introduction: Pregnancy in adolescents is a common reality faced by family, community and society, which can also bring health complications such as hypertension. Therefore, care of these teenagers is fundamental and can vary according to cultural contexts. Objective: To describe cultural care practices related to diet in pregnant adolescents with hypertension, who are inpatients in a Level III health care institution in Sincelejo (Colombia). Materials and methods: Qualitative ethnographic research. In-depth semi-structured interviews were done with thirteen participants. The ethnographic assessment facilitated the identification of terms, domains, taxonomies, and semantic relationships. Results: High consumption of traditional Caribbean food and processed products was observed. Care practices related to diet changes and their cultural meaning were common in subcategories such as healthy food and hypertension related diet. Conclusions: Diet care practices show diversity in terms of the cultural significance given by participants, which is an essential knowledge to provide coherent and humanized nursing care. Likewise, it is necessary to implement intervention programs to treat these patients both at home as well as at health care institutions.